Positively no Filipinos allowed building communities and discourse - Tiongson, Antonio T. 1968-.; Gutierrez, Edgardo V. (Edgardo Valencia) 1969-.; Gutierrez, Ricardo V. (Ricardo Valencia) 1971-. (Pasig City Anvil, 2008)
"Taken together, the essays in Positively No Filipinos Allowed vigorously pursue Filipino American critique. They insist that the forgetting that renders the Filipino American 'lost to history' must be made visible and intelligible."--Foreword by Lisa Lowe.
I. Imperial legacies and Filipino subjectivities -- 1. Patterns of reform, repetition and return in the first centennial of the Filipino Revolution, 1896--1996 / Jody Blanco -- 2. On Filipinos, Filipino Americans, and U.S. imperialism : interview with Oscar V. Campomones / Antonio T. Tiongson, Jr. -- 3. Filipino bodies, lynching, and the language of empire / Nerissa S. Balce -- 4. "Just ten years removed from a bolo and a breech-cloth" : the sexualization of the Filipino "menace" / Ruby C. Tapia -- II. Public policy, law, and the construction of Filipinos -- 5. Losing little Manila : race and redevelopment in Fiipina/o Stockton, California / Dawn Bohulano Mabalon. -- 6. Filipino Americans, foreigner discrimination, and the lines of racial sovereignty / Angelo N. Ancheta -- III. Reconfiguring the scope of Filipino politics -- 7. On the politics of (Filipino) youth culture : interview with Theodore S. Gonzalves / Antonio T. Tiongson, Jr. -- 8. Colonial amnesia : rethinking Filipino "American" settler empowerment in the U.S. colony of Hawai'I / Dean Itsuji Saranillo -- IV. Resignifying "Filipino American" -- 9. "A million deaths?" : genocide and the "Filipino American" Condition of Possibility / Dylan Rodriguez -- 10. Reflections on the trajectory of Filipino/a American studies : interview with Rick Bonus / Antonio T. Tiongson, Jr. -- 11. Do you mis(recognize) me : Filipina Americans in popular music and the problem of invisibility / Elizabeth H. Pisares -- 12. A different breed of Filipino balikbayans : the ambiguities of (Re-)turning / S. Lily Mendoza -- Notes -- About the contributors -- Index.
First published: 2006.
"This edition ... is published by arrangement with Temple University Press"--T.p. verso.
Copyright 2006 by Temple University; Philippine copyright 2008 by Temple University.
Keywords: Filipino Americans -- Ethnic identity; Filipino Americans -- History; Filipino Americans -- Social conditions; Community life -- United States; Racism -- United States; Imperialism -- Social aspects -- Philippines; United States -- Race relations; United States -- Relations -- Philippines; Philippines -- Relations -- United States; United States -- Insular possessions